Narrative Review: The Impact of Progress Test Examinations on Cummulative Grade Point Average (GPA) Among Medical Faculty Students - Rizqi Mubarok; Shulhana Mokhtar; Windy Nurul Aisyah (GLOBAL HEALTH SCIENCE GROUP, 2025)
The Progress Test (PT) is a standardized assessment tool used in medical education to evaluate cumulative knowledge and predict academic achievement, including Grade Point Average (GPA). This narrative review aims to examine the relationship between PT scores and the GPA of medical students. The literature search was conducted across PubMed, Embase, and manual sources, yielding 101 articles. After applying inclusion and exclusion criteria, 44 full-text articles with free access were reviewed, and 10 articles were selected for in-depth analysis. The selected studies discuss the impact of PT on learning strategies, knowledge retention, academic stress, and GPA outcomes. Most studies (9 out of 10) reported a positive correlation between PT scores and GPA, indicating that PTs can reflect students' cognitive development and academic readiness. However, factors such as test structure, learning approaches, and students’ understanding of PT purpose may influence its effectiveness. Overall, this review supports the role of PT as a formative and summative tool in assessing and enhancing academic performance.